The Art of Metaphor Translation: Taylor Swift's 'Willow' in Indonesian - Sumarga, Sresthi; Putri, Astari Amalia (Journal of Language, Literature and Teaching, 2024)
This research aims to help listeners understand the meaning of the lyrics of